How does multilevel upper airway surgery influence the lives of dogs with severe brachycephaly? Results of a structured pre- and postoperative owner questionnaire. (April 2016) - Pohl, Sabine; Roedler, Frauke S.; Oechtering, Gerhard U.
Highlights: Clinical signs of brachycephalic airway syndrome improved markedly in 62 dogs. Exercise tolerance improved markedly, while heat tolerance improved only modestly. Brachycephalic dogs benefit substantially from multi-level surgery. These dogs continue to exhibit certain welfare-relevant impairments despite surgery. Abstract: Brachycephalic airway syndrome in dogs is typified by a variety of anatomical abnormalities causing a diverse spectrum of clinical signs of varying intensity. This variability makes the assessment of the surgical outcome after upper airway surgery difficult. Using a structured questionnaire, the present study investigated the dog owner-perceived severity and frequency of a broad spectrum of welfare-relevant impairments 2 weeks before and 6 months after brachycephalic dogs underwent a recently developed multi-level upper airway surgery. All dogs underwent surgical treatment of stenotic nares (ala-vestibuloplasty), the nasal cavity (laser-assisted turbinectomy, LATE), the pharynx (palatoplasty and tonsillotomy), and if indicated, laryngeal surgery (laser-assisted ablation of everted ventricles and partial cuneiformectomy). Owners of brachycephalic dogs ( n = 102) referred for upper airway surgery were eligible to participate. Questionnaire data from owners of 37 Pugs and 25 French bulldogs were evaluated. In all dogs, the clinical signs associated with brachycephaly improved markedly after surgery. Most encouraging was the striking reduction in life-threatening events by 90% (choking fits decreased from 60% to 5% and collapse from 27% to 3%). The incidence of sleeping problems decreased from 55% to 3%, and the occurrence of breathing sounds declined by approximately 50%. There was a marked improvement in exercise tolerance and a modest improvement in heat tolerance. Dogs with severe brachycephaly benefitted substantially from multi-level surgery, and there were particular improvements in the incidences of severe impairment and life-threatening events. However, despite the marked improvement perceived by dog owners, these dogs remained clinically affected and continued to show welfare-relevant impairments caused by these hereditary disorders.